2017
DOI: 10.1080/07391102.2017.1348988
|View full text |Cite
|
Sign up to set email alerts
|

Different amyloid aggregation of smooth muscles titin in vitro

Abstract: A comparative study of amyloid properties of the aggregates of smooth muscle titin (SMT) from chicken gizzard was carried out. These aggregates were formed in two solutions: 0.15 M glycine-KOH, pH 7.2-7.4 (SMT(Gly)) and 0.2 M KCl, 10 mM imidazole, pH 7.0 (SMT(KCl)). Electron microscopy data showed that SMT aggregates has an amorphous structure in both cases. The results of atomic-force microscopy demonstrated slight differences in morphology in two types of aggregates. The SMT(Gly) aggregates were represented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 29 publications
3
12
0
Order By: Relevance
“…The non-specificity of CR as an amyloid dye was also shown in our in vitro studies [31]. We found that smooth muscle titin (SMT) from chicken gizzards can form amorphous aggregates in two different solutions containing: (i) 0.2 M KCl, 10 mM imidazole, pH 7.0 (SMT(KCl) aggregates) (Figure 2A) and (ii) 0.15 M glycine-KOH, pH 7.2–7.4 (SMT(Gly) aggregates) (Figure 2B).…”
Section: Exceptions To the Rulessupporting
confidence: 66%
See 3 more Smart Citations
“…The non-specificity of CR as an amyloid dye was also shown in our in vitro studies [31]. We found that smooth muscle titin (SMT) from chicken gizzards can form amorphous aggregates in two different solutions containing: (i) 0.2 M KCl, 10 mM imidazole, pH 7.0 (SMT(KCl) aggregates) (Figure 2A) and (ii) 0.15 M glycine-KOH, pH 7.2–7.4 (SMT(Gly) aggregates) (Figure 2B).…”
Section: Exceptions To the Rulessupporting
confidence: 66%
“…Interestingly, SMT(KCl) and SMT(Gly) aggregates, dialysed against a solution containing 0.6 M KCl, 30 mM KH 2 PO 4 , 1 mM DTT and 0.1 M NaN 3 at pH 7.0, also had amyloid X-ray patterns (Figure 2C,D). In both cases, ‘yellow to apple-green birefringence under polarised light’ was absent [31]. In our in vitro study, we did not observe a characteristic shift in the CR maximum optical absorbance from 490 to 540 nm in any sample, indicating the binding of the dye to titin amyloids [31].…”
Section: Exceptions To the Rulesmentioning
confidence: 79%
See 2 more Smart Citations
“…Previously, we have shown that 500-kDa SMT can form amorphous aggregates of a quaternary cross-β structure intrinsic to all amyloid aggregates [ 36 , 37 ]. We have also investigated the cytotoxicity of those aggregates [ 36 ].…”
Section: Introductionmentioning
confidence: 99%